Validation of process capabilities for directly acidified beef and venison containing beef snack sticks for control of E. coli O157:H7 - S.K. Stoltenberg; Kelly J.K. Getty; H. Thippareddi; T.M. Loughin; Randall K. Phebus (Kansas Agricultural Experiment Station Research Reports, 2005)
USDA/FSIS guidelines require sausage manufacturers to validate their processes to assure that they can achieve a five-log (99.999%) reduction of E. coli O157:H7. Some small meat processors use encapsulated acids instead of lactic acid starter cultures to produce directly acidified sausages. The objectives of this study were to determine 1) the effects of typical thermal processing temperatures and times on reducing E. coli O157:H7 in directly acidified all-beef and venison-containing beef snack sticks, 2) the effect of fat content (10 and 25%) on lethality, and 3) the effect of acid type (citric versus lactic) on lethality. For both all-beef and venison-containing beef snack sticks, E. coli O157:H7 reductions of approximately 3 log cycles (99.9%) were observed when product internal temperature reached 148 and 155ºF. Reductions increased to more than 5 log cycles after 2 hours of slow drying in which the smokehouse temperature was sequentially decreased to 70°F. Encapsulated citric acid was slightly more effective at lowering product pH, compared with the encapsulated lactic acid. Similar pathogen reductions were observed with 10 and 25% fat content. This study demonstrates that the defined processing schedule used to manufacture beef and venison-containing beef snack sticks is adequate to provide microbiologically safe products and to meet USDA guidelines for pathogen reduction. The processing schedule must include an extended drying phase, in addition to the thermal step, to meet these requirements.
Keywords: Cattlemen' s Day; 2005; Kansas Agricultural Experiment Station contribution; no. 05-144-S; Report of progress (Kansas State University. Agricultural Experiment Station and Cooperative Extension Service); 943; Beef; Acidified beef and venison; E. Coli O157:H7